Composite amnion for improving contracture after tissue repair operation

By constructing a three-layer composite structure of recombinant humanized collagen nanofiber membrane and human decellularized amniotic membrane, the problem of capsular contracture after breast implantation was solved, and the mechanical properties were enhanced, the degradation rate was controlled, and the biocompatibility was improved, significantly improving the tissue repair effect.

CN121243481AActive Publication Date: 2026-01-02SUN YAT SEN MEMORIAL HOSPITAL SUN YAT SEN UNIV +1

Patent Information

Application Number
CN202511822370.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-05
Publication Date
2026-01-02
Estimated Expiration
2045-12-05

AI Technical Summary

Technical Problem

Existing biomaterials are prone to triggering unpredictable immune responses and excessive foreign body reactions after breast implantation, leading to tissue inflammation and capsular contracture. Existing patch materials are scarce in source, expensive, have potential immunogenicity and disease transmission risks, and have insufficient mechanical properties or degradation mismatch.

Method used

A three-layer composite membrane consisting of recombinant humanized collagen nanofiber membrane and human decellularized amnion was formed by electrospinning and plasma treatment to create a composite structure with a fiber diameter of 100-150 nm. By optimizing the crosslinking agent ratio, the mechanical properties were enhanced and the degradation rate was controlled, thus forming an HdAM-RCC-HdAM structure.

Benefits of technology

It significantly inhibits radiotherapy-induced capsular contracture, reduces collagen deposition, lowers inflammatory response, promotes angiogenesis, improves tissue compliance, avoids the risk of animal-borne disease transmission, and has good biocompatibility and controllable degradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121243481A_ABST
    Figure CN121243481A_ABST
Patent Text Reader

Abstract

The invention discloses a composite amnion for improving contracture after tissue repair and a preparation method of the composite amnion. The composite membrane comprises a recombinant humanized collagen nanofiber membrane located in the middle layer and human decellularized amniotic membranes attached to the two faces of the nanofiber membrane. The composite membrane is prepared by preparing a recombinant humanized collagen nanofiber membrane through an electrostatic spinning technology and pressing the recombinant humanized collagen nanofiber membrane and a human decellularized amniotic membrane. The composite membrane has excellent mechanical properties and biological activity. Animal experiment results show that the composite film can effectively inhibit capsule contracture induced by radiotherapy, and the comprehensive effect of the composite film is obviously superior to that of a single-component material in the aspects of inflammation resistance, fibrosis resistance, degradation speed delaying, capsule compliance improving and the like. The composition can be used for improving the capsule contracture of the breast prosthesis, especially the capsule contracture induced by radiotherapy.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of biomedical materials, in particular to a composite film for tissue repair and application thereof in the preparation of medical devices, especially in the prevention or improvement of capsular contracture after breast implantation. BACKGROUND

[0002] In the field of regenerative medicine and tissue engineering, a good biomaterial for tissue regeneration should have good biocompatibility, biodegradability, excellent physical and chemical properties, and an ideal three-dimensional network structure, and should also have the characteristics of promoting angiogenesis and soft tissue repair. However, many implanted biomaterials, such as breast implants, often cause unpredictable immune responses and excessive foreign body reactions, leading to tissue inflammation, contracture, and other conditions.

[0003] Breast cancer is one of the most common malignant tumors in women. With the improvement of treatment level, patients not only pursue survival rate, but also put forward higher requirements for postoperative life quality and physical restoration. Implant breast reconstruction surgery has become a common surgical procedure due to its small surgical trauma and fast recovery. However, implants as foreign bodies can cause foreign body reactions in the body, and eventually form a fibrous capsule around the prosthesis. When the fibrous capsule is excessively fibrotic and contracts, it leads to capsular contracture, which is clinically manifested as breast hardening, deformation, and pain. In severe cases, reoperation is required, which brings great physical and mental pain and economic burden to patients. Studies have shown that about 40% of patients with prosthetic breast reconstruction will undergo secondary surgery due to severe capsular contracture.

[0004] To address this challenge, breast patches have been introduced in clinical practice. Commonly used breast patches include biological patches and non-biological patches. Biological patches, such as acellular dermal matrix (ADM), can not only provide sufficient tissue coverage, but also have biological activity that helps to reduce the occurrence of capsular contracture. However, the current mainstream human or animal-derived ADM has inherent defects such as scarcity of sources, high price, potential immunogenicity, and risk of disease transmission. Non-biological patches, such as synthetic patches, are generally less expensive, but lack biological activity and cannot actively induce tissue repair. Moreover, their degradation products can cause chronic inflammation, and their preventive effect on capsular contracture is controversial.

[0005] Human decellularized amniotic membrane (HdAM) as a natural biomaterial has extremely low immunogenicity, abundant biological active factors, and good anti-inflammatory and anti-fibrotic properties, showing potential as an ideal patch. However, its poor mechanical strength and rapid in vivo degradation limit its application in areas requiring long-term support. The emergence of recombinant humanized collagen has brought hope for solving the immunogenicity problem of animal-derived collagen, but it also has problems of insufficient mechanical properties or mismatched degradation rate when formed into a film alone.

[0006] Therefore, there is an urgent need in the art to develop a new type of biological composite membrane patch, which should have excellent mechanical properties, controllable degradation rate, good biocompatibility, and active anti-inflammatory and anti-fibrosis biological functions, so as to effectively prevent and improve capsular contracture. SUMMARY

[0007] The purpose of the present application is to overcome the shortcomings of the prior art, provide a composite membrane with enhanced mechanical properties, controllable degradation, good biocompatibility, and effective inhibition of capsular contracture, as well as a preparation method and application thereof.

[0008] To achieve the above-mentioned purpose, the technical scheme adopted by the present application is as follows:

[0009] In a first aspect, the present application provides a composite membrane (referred to as CC) for improving contracture after tissue repair surgery. The composite membrane comprises a recombinant humanized collagen nanofiber membrane in the middle layer, and human acellular amniotic membranes attached to both sides of the recombinant humanized collagen nanofiber membrane, forming a three-layer structure wrapped by human acellular amniotic membranes on the inside and outside. Among them, the average fiber diameter of the recombinant humanized collagen nanofiber membrane is 100-150 nm, preferably the average fiber diameter is 113.11±2.08 nm.

[0010] Preferably, the average fiber diameter of the entire composite membrane is 10-20 nm, preferably 15.44±0.24 nm.

[0011] Preferably, the composite membrane exhibits excellent mechanical properties and controllable degradation rate, with an elastic modulus not less than 8 MPa, and a degradation rate not higher than 60% after in vitro degradation in collagenase solution for 7 days, preferably between 50%-60%.

[0012] In a second aspect, the present application provides a preparation method of the composite membrane: sequentially laminating human acellular amniotic membranes and recombinant humanized collagen nanofiber membranes to form a three-layer structure, performing compression treatment, freeze-drying, and obtaining the composite membrane.

[0013] The preparation method of the recombinant humanized collagen nanofiber membrane comprises the following key steps: 1. The recombinant humanized collagen is dissolved in a 50% (v / v) ethanol aqueous solution at a concentration of 30-40% (w / v), electrospinning is carried out at a push-in speed of 0.1-0.2 mm / min, and an original nanofiber membrane is obtained. 2. The fiber membrane is subjected to plasma treatment to activate the surface. The plasma treatment parameters are as follows: oxygen inlet pressure 0.1 MPa, inlet flow rate 30 ml / min, chamber pressure 25 Pa, radio frequency power 20 w, and treatment time 5 min. 3. The original fiber membrane is crosslinked using a crosslinking solution with a concentration of 1.5 WT% and a molar concentration ratio of EDC to NHS of 5:2 (the solvent is 90.0% anhydrous ethanol). In a third aspect, the application provides an application of the composite membrane in the preparation of a medical device. The medical device is preferably a breast patch or a breast prosthesis, which is used for preventing or improving postoperative contracture, in particular radiotherapy-induced capsular contracture.

[0014] The human decellularized amniotic membrane (HdAM) involved in the application is the innermost layer of human placenta, is a transparent, nerve-free, blood vessel-free, lymph vessel-free and tough tissue, and is a fully decellularized amniotic membrane obtained after full decellularization.

[0015] The recombinant humanized collagen involved in the application is a recombinant collagen obtained by optimizing and splicing codons based on the collagen protein of human skin as the original gene sequence and optimizing and screening the advantageous part (for example, the part with high water solubility, high biological activity and / or good permeability).

[0016] The recombinant humanized collagen nanofiber membrane (RCC) involved in the application refers to a porous thin film material prepared by taking the recombinant humanized collagen as the main raw material and through electrospinning and other technologies, and the average diameter of the fiber is in the nanometer level. The microstructure is a three-dimensional network structure formed by a large number of nanofibers randomly interlaced.

[0017] The application has the following beneficial effects:

[0018] 1. Process innovation, structural innovation and performance synergy: By optimizing the electrospinning parameters (such as specific injection speed), the proportion of cross-linking agent and the introduction of plasma treatment, RCC with an average fiber diameter of 100-150 nm is formed. The fiber diameter of the composite amniotic membrane (CC) obtained by pressing HdAM and RCC is significantly reduced, with an average diameter of about 15.44±0.24 nm, and arranged closely to form a large number of pores, forming a unique "HdAM-RCC-HdAM" three-layer composite structure. The combination of the excellent biological activity of HdAM and the nanofiber scaffold advantage of RCC significantly enhances the mechanical properties (elastic modulus increases by more than ten times), while retaining its anti-inflammatory and anti-fibrosis biological functions to the greatest extent, and effectively delaying the degradation rate. 2. Significant effect: Animal experiments show that the composite membrane can significantly inhibit radiation-induced capsular contracture, with the thinnest capsular thickness, reduced collagen deposition, down-regulated expression of fibrosis markers (TGF-β, α-SMA), reduced inflammation (MPO and IL-10), improved capsular compliance (decreased collagen type I / III ratio), and promoted neovascularization (increased α-SMA + vascular density), with a comprehensive effect better than single-component materials. The composite membrane of the present application can be used specifically for the prevention and treatment of capsular contracture of breast prosthesis, especially for radiation-induced capsular contracture and tissue repair applications that require a long time. 3. Safe source and ethical advantage: The use of recombinant humanized collagen and human amniotic membrane avoids the risk of animal-derived disease transmission and serious ethical controversy, and has a relatively abundant source, controllable quality, environmentally friendly process, good reproducibility, and industrialization potential. BRIEF DESCRIPTION OF DRAWINGS

[0019] Figure 1 is a morphology observation diagram of human decellularized amniotic membrane (HdAM), recombinant humanized collagen nanofiber membrane (RCC) and composite membrane (CC).

[0020] Figure 2 is a scanning electron microscope (SEM) diagram of HdAM, RCC and CC, showing the micro-surface morphology and fiber diameter distribution of the material.

[0021] Figure 3 is a mechanical property test result diagram of HdAM, RCC and CC. Figure 4 is an in vitro degradation curve diagram of HdAM, RCC and CC in collagenase solution.

[0022] Figure 5 is a diagram showing the adhesion and proliferation of different cells on HdAM, RCC and CC by Calcein-AM / PI double staining method.

[0023] Figure 6 is a general observation diagram of radiation-induced capsular contracture.

[0024] Figure 7 Figure 1 is a graph showing the effect of CC on reducing radiation-induced capsular formation and collagen deposition.

[0025] Figure 8 Figure 2 is a graph showing the effect of CC on reducing fibrosis at the capsular site and promoting neovascularization.

[0026] Figure 9 Figure 3 is a graph showing the effect of CC on reducing radiation-induced inflammation in the capsular tissue.

[0027] Figure 10 Figure 4 is a graph showing the effect of CC on improving the compliance of the capsular tissue (ratio of collagen type I / III content). DETAILED DESCRIPTION

[0028] The technical solutions of the present application will be described in detail below with reference to the accompanying drawings and examples, but the protection scope of the present application is not limited thereto. Those skilled in the art should understand that the described embodiments can be modified without departing from the principles of the present application, and these modifications should also be considered to fall within the protection scope of the present application.

[0029] Example 1: Preparation of human decellularized amniotic membrane (HdAM)

[0030] The blood stains on the amniotic membrane surface were washed clean and placed in a stainless steel tray. A 0.1% (w / v) neutral protease PBS solution 500 mL was prepared and the amniotic membrane surface was fully soaked. It was incubated in a 37°C biochemical incubator for 30 min. After incubation, it was washed with PBS for 3 times. The cell debris on the front and back surfaces was gently scraped off with a cell scraper. The obtained decellularized amniotic membrane (HdAM) was washed with PBS for 3 min and then prepared for use. No cell residues were observed by HE staining and scanning electron microscopy.

[0031] Example 2: Preparation of recombinant humanized collagen nanofiber membrane (RCC)

[0032] The recombinant humanized collagen was dissolved in 50% (v / v) ethanol aqueous solution at a concentration of 35% (w / v), stirred at room temperature overnight, and prepared into a clear and transparent electrospinning solution. A 10 mL syringe equipped with a 21G stainless steel needle was used to fix the spinning solution in the electrospinning device. The spinning parameters were set as follows: reciprocating stroke 80 mm, translation speed 250 mm / min, spinning solution injection speed 0.15 mm / min, rotating receiver speed 100 rpm / min, positive voltage +9 kV, and negative voltage -7 kV. Electrospinning was performed to obtain the original recombinant humanized collagen nanofiber membrane (RCC). Scanning electron microscopy showed that the RCC fibers were continuous and uniform, had an ideal void size, and the average diameter was about 113.11±2.08 nm.

[0033] Example 3: Preparation of recombinant humanized collagen composite amniotic membrane (CC)

[0034] Surface plasma treatment of RCC obtained in Example 2: Place the RCC flat on the quartz piece holder of the plasma cleaner, mark the upper surface of the nanofiber membrane, and place it in the cavity of the plasma cleaner. Open the oxygen valve and turn on the plasma cleaner switch. Turn on the vacuum pump and observe the air pressure value in the vacuum pressure gauge. When the chamber is reduced to 300 mTorr, open the oxygen inlet valve. Stop when the air pressure rises to 350-450 mTorr. Rotate the RF level to MED and process for 5 minutes. When the timer is up, rotate the RF level to OFF. Turn off the vacuum pump and rotate the angle valve until the chamber door is opened. Take out the nanofiber membrane and store it in a disposable petri dish in the dark. Repeat the above operation on the other side of the nanofiber membrane. The plasma treatment parameters are: oxygen inlet pressure 0.1 MPa, inlet flow rate 30 ml / min, chamber pressure 25 Pa, RF power 20 w, processing time 5 min.

[0035] Chemical crosslinking of RCC with EDC / NHS: Dissolve EDC and NHS in 90.0% anhydrous ethanol at a molar ratio of 5:2 to prepare a 1.5 WT% EDC / NHS crosslinking solution. Use 10 mL of the crosslinking solution to fully wet the RCC (5 cm x 8 cm), and react at 20°C for 24-48 h. After crosslinking is complete, remove the RCC, wash it with PBS three times, and then vacuum dry it.

[0036] Lay HdAM on the silicone paper (matrix side up), lay the crosslinked RCC on top of it, and then lay HdAM (matrix side down) on top of the RCC to form a three-layer structure. Place the composite structure on the operating table of the pneumatic press, and apply a pressure of 27 kPa. After pressing, place it at 4°C for 20-24 h. After the composite membrane reaction is complete, remove the silicone paper, wash it with PBS three times, freeze-dry the composite membrane, and obtain the dried composite membrane (CC). Scanning electron microscopy shows that the fibers on the surface of CC are closely arranged, with an average diameter of about 15.44 ± 0.24 nm.

[0037] The morphology of the prepared human decellularized amniotic membrane (HdAM), recombinant humanized collagen nanofiber membrane (RCC), and composite membrane (CC) is shown in Figure 1 The scanning electron microscopy (SEM) images of the surface morphology of the three materials and the fiber diameter distribution frequency histogram of RCC and CC are shown in Figure 2 Figure 2 ​In the middle, a-c are HdAM, RCC, CC scanning electron microscopy whole map, scale is 30 μm; d-f is HdAM, RCC, CC local scanning map, scale is 5 μm; g and h are RCC, CC fiber diameter distribution frequency histogram.

[0038] Example 4: Performance test of composite film

[0039] Mechanical properties test was performed on HdAM, RCC and CC. As shown in Figure 3 , the elastic modulus of CC was the highest, reaching 10.16±1.27 MPa, which was significantly higher than that of HdAM (0.88±0.8 MPa) and RCC (2.23±0.12 MPa). The ultimate tensile strength of CC was 3.52±0.59 MPa, which was also significantly better than the other two groups.

[0040] The in vitro degradation experiment results are shown in Figure 4 , after incubation in collagenase solution for 7 days, HdAM was basically completely degraded (degradation rate 89.1%), while the degradation rate of CC was only 55.1%, and that of RCC was 60.6%, proving that CC has more stable anti-degradation ability.

[0041] The results of cell compatibility experiment (Calcein-AM / PI double staining method) are shown in Figure 5 , mouse monocyte macrophage leukemia cells Raw264.7, human skin fibroblasts HSF, and human umbilical vein endothelial cells HUVEC all can adhere, grow and proliferate normally on CC, proving that CC has good biocompatibility.

[0042] Example 5: Effect verification of composite film on reducing radiation-induced capsular contracture in animal model

[0043] Animal model establishment:

[0044] 1. Prosthesis implantation

[0045] The experiment was divided into 4 groups: simple prosthesis implantation group (Blank group), HdAM, RCC and CC combined prosthesis implantation group, 6 rats in each group;

[0046] Anesthesia: After inducing anesthesia of rats with 3%-5% concentration of isoflurane, the rats were placed on a small animal operating table, and anesthesia was maintained with 2-3% concentration of isoflurane, and the rats were kept warm with a warming blanket; the right upper back hair was shaved, with an area of about 5x5 cm.

[0047] Disinfection and draping: after 3 times of disinfection with 5% iodophor, sterile surgical drapes were laid;

[0048] Prosthesis implantation: make a surgical incision of about 3 cm near the second pair of breasts on the back, implant the prosthesis and material-wrapped prosthesis into the rat breast fat pad, and fix the implant on the surrounding tissue in the RCC and CC groups;

[0049] Suture: suture subcutaneous tissue and skin layer by layer, cover the incision with sterile gauze, and strictly perform sterile operation technique during the operation.

[0050] Postoperative care: give cefquinome sodium for anti-infection (0.2 mg / kg) and meloxicam for analgesic treatment (0.3 mg / kg) for 3 consecutive days after the operation. Observe the healing of the incision and whether there are signs of infection such as increased skin temperature, redness and swelling at the implant site.

[0051] 2. Radiation-induced capsular contracture

[0052] After 7 days of prosthesis implantation, check whether the incision is completely healed and whether there are signs of infection such as redness, fever and increased skin temperature around the prosthesis. Perform X-ray irradiation on the prosthesis implant site to induce capsular contracture. The specific operation steps are as follows:

[0053] (1) Anesthesia: perform intraperitoneal injection of tribromoethanol for anesthesia;

[0054] (2) X-ray irradiation: place the rat flat on the small animal irradiation instrument loading table, adjust the height of the emitter and the loading table, the irradiation range is 4*4 cm, and the parts that do not need to be irradiated are blocked by lead plates; adjust the X-ray energy, and perform single irradiation with 20 Gy energy;

[0055] (3) After the irradiation is completed, pay attention to give the experimental animal heat preservation and promote wake-up;

[0056] (4) Within 1 week after the irradiation is completed, observe the mental state of the experimental animal once every 2-3 days, and whether there are signs of radiation dermatitis damage such as redness and ulceration at the irradiated site.

[0057] (5) After 3 months, take the capsule tissue around the prosthesis.

[0058] (6) Prepare the taken specimens into paraffin sections for subsequent research.

[0059] Experimental results

[0060] 1. General observation of the capsule tissue, the experimental results are shown in Table 1: Figure 6 The Blank group that did not receive radiotherapy and the Blank-IR group that received radiotherapy can both see obvious double capsules, and the blood vessels on the surface of the Blank-IR group are less than those of the Blank group; the other radiotherapy groups do not show obvious double capsule phenomenon. The blood vessel formation in the CC-IR group is obviously increased compared with other groups.

[0061] 2. Capsular tissue thickness and collagen deposition, as shown in Figure 7 (a is the representative graph of the thickness of the capsular tissue; b is the representative graph of collagen deposition in the capsular tissue; c is the statistical analysis graph of the thickness of the capsular tissue; d is the statistical analysis graph of collagen deposition) shows that through HE staining, the thickness of the capsule of the Blank-IR group is significantly increased compared with the Blank group, indicating that the radiotherapy-induced capsular contracture modeling is successful. The thickness of the capsule of the Blank-IR group is 226.25 ± 23.18 μm, while that of the Blank group is 149.29 ± 6.57 μm, and the difference is statistically significant. The thickness of the capsule of each material group receiving radiation is, HdAM group: 105.34 ± 10.40 μm, RCC group: 135.63 ± 6.16 μm, and CC group is the thinnest, only 55.16 ± 6.43 μm. The difference between Blank-IR and the remaining radiotherapy groups is statistically significant.

[0062] Masson staining results show that the collagen fibers in the Blank-IR group are dense and in thick cord-like shape, arranged in parallel; the amount of collagen fibers deposited in the remaining three radiotherapy groups is significantly reduced compared with the Blank-IR group, the collagen density in the HdAM group is larger than that in the RCC and CC groups, and the fibers are arranged more compactly; the collagen fibers in the RCC and CC groups are fine and loose, and there are scattered red-stained cellulose and other tissues in the collagen, and the material integrated with the tissue can be seen in the capsular tissue.

[0063] 3. CC reduces fibrosis at the capsule and promotes neovascularization, as shown in Figure 8 (a is the representative graph of TGF-β and α-SMA expression in the capsular tissue; b is the statistical analysis graph of TGF-β; c is the statistical analysis graph of α-SMA; d is the statistical analysis graph of α-SMA + blood vessel density) shows that TGF-β is a direct inducer of fibrosis, and the expression of TGF-β in the capsule of each group shows that the expression of TGF-β in the Blank-IR capsule is significantly increased compared with the Blank group, and the difference is statistically significant; the TGF-β in the remaining three groups of capsular tissue is reduced compared with the Blank-IR group, and the difference is statistically significant.

[0064] Continuous activation of myofibroblasts is the initiating factor of capsular contracture. By analyzing the expression of α-SMA in the capsular tissue of each group, it is found that the expression of α-SMA in the Blank-IR group receiving radiotherapy is significantly increased compared with the Blank group, and the difference is statistically significant; the expression of α-SMA in the material combined implantation group is reduced compared with the Blank-IR group, and the difference is statistically significant. The α-SMA + blood vessel density of the RCC and CC groups is significantly increased compared with the other groups.

[0065] 4. CC reduces radiotherapy-induced inflammation of the capsular tissue, as shown in Figure 9(a is the expression of inflammatory factor MPO and anti-inflammatory factor IL-10 in the encapsulating tissue; b is the statistical analysis diagram of MPO expression; c is the statistical analysis diagram of IL-10 expression) shows that encapsulation contracture is the result of persistent inflammation stimulation. As shown in the figure, compared with the Blank group, radiotherapy can obviously induce tissue inflammation, and the expression of MPO is significantly increased. The MPO of the Blank-IR group is increased by 3 times compared with the Blank group, and the difference is statistically significant. The expression of MPO in the HdAM-IR and RCC-IR groups is 60% of that in the Blank-IR, and the MPO in the CC group is reduced most significantly, about 1 / 3 of that in the Blank-IR encapsulation, and the difference is statistically significant, indicating that CC can significantly reduce the inflammation of the encapsulation tissue induced by radiotherapy.

[0066] IL-10 is a kind of anti-inflammatory cytokine, which plays an important role in the regulation of inflammation. The expression of IL-10 in the encapsulation tissue was detected, as shown in the figure, compared with the Blank group, in the four groups receiving radiotherapy, the expression of IL-10 in the HdAM-IR and CC-IR groups was similar, slightly decreased, while the expression of Blank-IR and RCC-IR was significantly reduced, about 50% of that in the HdAM-IR and CC-IR groups.

[0067] 5. CC improves the compliance of the encapsulation tissue induced by radiotherapy, as Figure 10 (a is the expression of Blank group encapsulation tissue type I and III collagen content; b is the expression of type I and III collagen content in the encapsulation of each group receiving radiotherapy; c is the statistical analysis diagram of the difference of type I and III collagen content ratio in the encapsulation tissue) shows that the content ratio of type I and III collagen in the encapsulation tissue is a good indicator for predicting the compliance of the encapsulation. By type I and III collagen immunofluorescence co-staining, it is found that in the four groups receiving radiotherapy, the type I collagen in each encapsulation has different degrees of increase, especially in the Blank-IR group, compared with the Blank group, there are a large number of type I collagen distributed in the inner and outer encapsulation, especially in the inner encapsulation, the type I collagen fibers are thick and closely arranged. The results of type I and III collagen content ratio in each group show that the type I and III collagen content ratio in the Blank-IR group is increased by 4.3 times compared with the Blank group, and the difference is statistically significant. While the content ratio in the HdAM-IR group is similar to that in the Blank group, which is 4.4%, and the content ratio in the RCC-IR and CC-IR groups is significantly decreased compared with the Blank-IR group, which is 2.9% and 2.5% respectively, and the type I and III collagen content ratio in the three material groups is statistically different from that in the Blank-IR group.

Claims

1. A composite amniotic membrane for improving postoperative contracture after tissue repair surgery, characterized in that: The composite amnion comprises a recombinant humanized collagen nanofiber membrane in the middle layer, and a decellularized human amnion membrane attached to both sides of the recombinant humanized collagen nanofiber membrane; wherein the recombinant humanized collagen nanofiber membrane is obtained by electrospinning, and its fiber average diameter is 100-150 nm.

2. The composite amnion as described in claim 1, characterized in that: The composite amnion has an average fiber diameter of 10-20 nm.

3. The composite amnion as described in claim 1 or 2, characterized in that: The elastic modulus of the composite amniotic membrane is not less than 8 MPa; the degradation rate of the composite amniotic membrane after 7 days of in vitro degradation in collagenase solution is 50-60%.

4. The composite amnion as described in any one of claims 1-3, characterized in that... The preparation method of the composite amnion recombinant humanized collagen nanofiber membrane includes the following steps: (1) Electrospinning: Recombinant humanized collagen was dissolved in 50% (v / v) ethanol aqueous solution at a concentration of 30-40% (w / v) to prepare an electrospinning solution. Electrospinning was carried out at a solution injection speed of 0.1-0.2 mm / min to obtain the original recombinant humanized collagen nanofiber membrane. (2) Plasma treatment: The recombinant humanized collagen nanofiber membrane is subjected to plasma treatment to obtain the target recombinant humanized collagen nanofiber membrane. (3) Crosslinking reaction: The plasma-treated recombinant humanized collagen nanofiber membrane is immersed in a crosslinking solution containing 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS) to carry out the crosslinking reaction, thereby obtaining a crosslinked recombinant humanized collagen nanofiber membrane; the concentration of the crosslinking solution is 0.05-0.5 M, and the molar ratio of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) to N-hydroxysuccinimide (NHS) is 5:

2.

5. The composite amnion as described in claim 4, characterized in that... The electrospinning parameters for the preparation method of the recombinant humanized collagen nanofiber membrane are as follows: reciprocating stroke of 80 mm, translation speed of 250 mm / min; spinning solution injection speed of 0.15 mm / min; rotational speed of the roller receiver of 100 rpm / min, positive voltage of +9 kV, and negative voltage of -7 kV.

6. The composite amnion as described in claim 4, characterized in that... The specific steps of the crosslinking reaction in the preparation method of the recombinant humanized collagen nanofiber membrane are as follows: 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS) are dissolved in 90% anhydrous ethanol at a molar concentration ratio of 1:1 to prepare a 0.1 M crosslinking solution. The original recombinant humanized collagen nanofiber membrane was fully immersed in the crosslinking solution for 24 hours. After washing and vacuum drying, the crosslinked recombinant humanized collagen nanofiber membrane was obtained.

7. The composite amnion as described in claim 4, characterized in that... The plasma treatment parameters for the preparation method of the recombinant humanized collagen nanofiber membrane are as follows: oxygen inlet pressure 0.1 MPa, inlet flow rate 30 ml / min, chamber pressure 25 Pa, radio frequency power 20 W, and treatment time 5 min.

8. The method for preparing the composite amnion according to any one of claims 1-3, characterized in that, Includes the following steps: (1) Provide decellularized human amnion; (2) Provide recombinant humanized collagen nanofiber membranes; (3) Human decellularized amnion and recombinant humanized collagen nanofiber membrane are stacked in sequence to form a three-layer structure, and then pressed and freeze-dried to obtain the composite amnion.

9. The application of the composite amniotic membrane as described in any one of claims 1-3 in the preparation of medical devices, characterized in that: The medical device includes a breast patch, a breast implant, or a breast implant capsule.

10. The application as described in claim 9, characterized in that: The medical device is used to improve postoperative contractures after tissue repair surgery; wherein the contractures are radiotherapy-induced contractures.

Citation Information

Patent Citations

  • Tissue patch and preparation method thereof

    CN101366979A

  • Electrospinning recombinant humanized III-type collagen wound dressing and preparation method thereof

    CN116271182A

  • Preparation method of acellular matrix containing bioactive coating

    CN120733122A

Cited By

  • Collagen injection for tendon repair based on coaxial neutralization microchannel fiber forming and preparation method thereof

    CN122097691A